Designing a low cost microcontroller-based device for multipurpose learning - Arefin, Ahmed Shamsul; Habib, K.M. Masum; Sultana, Razia; Lutful Kabir, S.M. (Proceedings of 10th International Conference on Computer and Information Technology (ICCIT 2007), 27-29, December 2007, United International University, Dhanmondi, Dhaka-1209, Bangladesh, 2007)
A low cost microcontroller based device for multipurpose electronic learning has been developed. This paper describes the design methodology and the development of its hardware and software. Four applications and the development of the general purpose device have been explained in this paper. The technique presented can be applied, following the approach described in a small or in a large project.